How to overcome «the surgical treatment» and not to cut - G. D. Tsesarskaya (Бюллетень сибирской медицины)
The questions of industrial property commercialization in the sphere of medicine are discussed. The reasons according to which the patenting of inventions in the sphere of medicine occurs with legal and financial difficulties are pointed out. The author of the article proposes several ways to overcome difficulties appearing when new preparations, equipment and the methods of treatment are inserted.